EU ‘DEEP’ PERIPHERY: A CASE STUDY OF MOUNTAIN BORDERLANDS IN BULGARIA - BOIAN KOULOV (Revue Roumaine de Géographie)
Geographic research and constant monitoring of EU periphery and its dynamics are necessary to identify and outline priority areas for regional development policy. This work proposes that “deep” periphery areas form where peripheries of a different geographic nature (physical, economic, political) and scale overlap. The investigation applies GIS-aided mapping and comparative scale analysis to the case study of Bulgaria to identify “deep” periphery areas and affirm that they are disproportionally situated in the mountain regions along the EU external borders. These study results suggest special regional development policy attention to such areas, among which adoption of a Mountain Sustainable Development Strategy for all mountains within the EU geographic space, and, in particular, a Southeast European Convention on Sustainable Development of Mountain Regions.